Role of the γ′′ precipitation at the cell boundaries in enhancing the creep resistance of additively manufactured Inconel 718 alloy using the laser powder bed fusion technique - Liu, Fei (2024)
Laser powder bed fusion (LPBF) manufactured Inconel 718 superalloy (IN718) parts exhibit inferior creep properties compared to their conventionally manufactured (CM) counterparts due to the unique microstructural features associated with them. In this study, two different heat treatment schedules were employed, to critically examine role of distinct microstructural features associated with LPBF on the creep performance of LPBF IN718. Experimental results reveal that the creep performance is controlled by the Laves and γ′′ phases, as well as the cellular structure. Specially, the effective dissolution of Laves phases that are distributed along the grain and cellular boundaries in the as-fabricated state during solution treatment reduces the cavity nucleation sites and hence, extends the creep lifetime. The release of Nb into the matrix contributes to the precipitation of primary strengthening γ′′ phase during subsequent aging, enhancing the creep resistance. More importantly, the formation of a unique cellular structure with densely distributed γ′′ phase along the cellular boundaries, which exhibits high impediment of dislocation movement and inhibition of crack propagation, results in superior creep performance. The findings of the current study provide an effective heat treatment strategy for achieving high creep performance in LPBF nickel-based superalloys.